“Capacidades estatais, arranjos institucionais e instrumentos da ação pública : a política de regionalização de turismo de Minas Gerais” - Roberta Graziella Mendes Queiroz (2022)
This thesis aims to understand the factors that explain the results of the implementation of tourism regionalization in Minas Gerais, from 2003 to 2020. The main theory of this study focuses on discussions about state capacity and its effects on the production of public policies. Two dimensions can be observed more briefly: (i) an organizational bureaucratic dimension of capacity that considers the essentiality of the organizational structure and competent bureaucratic officials; and (ii) the relational dimension, in which an idea of capacity comes closer to the notion of governance, based on the verification of the need for integration between different actors (state or not) that act in the construction of policies, and relational capacity of State. In line with this last dimension, we may consider the role of institutional arrangements of the policy and the instruments of public action in the production of implementation instruments. Considering the dimensions given, the current hypotheses are: 1) the results of the implementation of the Minas Gerais' tourism region policy are influenced by the state capacity of the Secretary of State for Tourism and Culture of Minas Gerais, especially its organizational-bureaucratic capacity, expressed, among other aspects, by the management, articulation, and coordination of policy at the state level; (2) the institutional arrangements of the policy, at the state and regional levels, affect the results of its implementation and tend to develop new capacities, which, at the regional level, materialize in relational capacities between the actors involved in the performance of the policy; and (3) the instruments of the public action related to the policy, defined in the statal scenario, produce constraints and incentives for actors at the regional and municipal level of policy implementation, thus affecting their behavior, their form of articulation and, consequently, their relational capacity and the results of policy implementation. The following methodological strategies were adopted: document analysis and semi-structured interviews with state government actors and regional actors, participants in the policy of two instances of regional planning in the design of the policy. In general, the current findings confirm the hypotheses of the study. However, was observed that other capacities and structural characteristics were also key to successful policy implementation.